ANTIXENOSIS AND ANTIBIOSIS EFFECTS OF SELECTED RICE CULTURES AGAINST THE BROWN PLANTHOPPER (NILAPARVATA LUGENS (STÅL)) - K , VASANTA BHANU (The Journal of Research ANGRAU, 2026)
Pot culture experiments were carried out in glasshouse at Andhra Pradesh Rice Research Institute and Regional Agricultural Research Institute, Maruteru, West Godavari district, Andhra Pradesh during the period 2010 to 2011 to study the antixenosis and antibiosis effects of twelve rice cultures on rice brown planthopper feeding activity along with resistant check (Ptb 33) and susceptible check (TN1). Among those, the rice cultures which recorded significantly maximum number of feeding marks were MTU 1075 (128.10), MTU IJ 206-7-4-1 (112.80), MTU PLA 99-1-3 1-2 (110.20) and resistant check, Ptb 33 (61.50) than TN1 (24.30). The rice cultures, MTU IJ 206-7-4-1 (25.60 mm2), Ptb 33 (58.80 mm2), NLR 3093 (65.60 mm2) and RGL 7002 (87.80 mm2)excreted significantly less amount of honeydew compared to the susceptible culture, TN1 (450.40 mm2) indicating that these were less preferable for BPH feeding.